Biotic interactions with mycorrhizal systems as extended nutrient acquisition strategies shaping forest soil communities and functions - Netherway, Tarquin; Bengtsson, Jan; Krab, Eveline J.; Bahram, Mohammad (Basic and applied ecology, 2021)
Plant nutrient acquisition strategies involving ectomycorrhizal (EcM) and arbuscular mycorrhizal (AM) associations, are key plant functional traits leading to distinct carbon (C) and nutrient dynamics in forests. Yet, little is known about how these strategies influence the structure and functioning of soil communities, and if such mycorrhizal effects may be more or less pronounced depending on the type of forest and various abiotic factors. Here we explore the potential interactions occurring between plant-EcM and plant-AM systems with the diverse soil organisms occurring in forest soils, and in the process draw attention to major issues that are worthy for future research directions. Based on these potential interactions, we suggest that EcM systems, especially those involving gymnosperms in colder climates, may select for a soil community with a narrow set of functions. These EcM systems may exhibit low functional redundancy, dominated by symbiotic interactions, where EcM fungi maintain low pH and high C/N conditions in order to tightly control nutrient cycling and maintain the dominance of EcM trees. By contrast, AM systems, particularly those involving deciduous angiosperm trees in mild and warmer climates, may facilitate a functionally more diverse and redundant soil community tending towards the dominance of competitive and antagonistic interactions, but also with a range of symbiotic interactions that together maintain diverse plant communities. We propose that the contrasting belowground interactions in AM and EcM systems act as extended nutrient acquisition traits that contribute greatly to the prevailing nutrient and C dynamics occurring in these systems.